Numerical study on the effect of a lobed nozzle on the flow characteristics of submerged exhaust. Issue 1 (May 2016) - Miao, T C; Du, T; Wu, D Z; Wang, L Q
Abstract: In order to investigate the effecting mechanism of nozzle structure on the flow characteristics of submerged exhaust, the processes of air exhausted from a lobed nozzle and a round nozzle into water have been numerically simulated using realizable k – ε model under the framework of the volume of fluid (VOF) model. Both the flow structure and the upstream pressure fluctuations are taken into consideration. The calculated results are in good agreement with the experimental results, showing that gas exhausted from the lobed nozzle would flow along the axial direction easier. Flow structure of the gas exhausted from the lobed nozzle is more continuous and smoother. The pressure fluctuations in the upstream pipeline would also be reduced when gas exhausted from the lobed nozzle. The resulting analysis indicates that the lobed structure could deflect water flow into the gas jet. The induced water would be mixed into the gas jet in form of small droplets, making the jet more continuous. As a result, the mixed jet flow would be less obstructed by the surrounding water, and the upstream pressure fluctuation would be reduced. The work in this paper partly explained the effecting mechanism of nozzle structure on the flow characteristics of submerged exhaust. The results are useful in the designing of exhaust nozzles.